Infarct core growth rate and 90-day outcomes in ischemic stroke: subgroup analysis based on onset-to-recanalization time - Chen, Sha; Chen, Guofang; Zhao, Changzhi; Wang, Enle; Zhou, Yewen; Ding, Manhua; Zhang, Yang (Frontiers in Neurology, 2025)
BackgroundIt is essential to understand the factors that influence patient outcomes in stroke research. The infarct core growth rate (ICGR) is emerging as a potentially valuable marker, but its relationship with patient outcomes, especially concerning the onset-to-recanalization time (ORT), requires further clarification. This study investigates the impact of ICGR on 90-day (90d) outcomes in acute ischemic stroke patients and explores whether stratifying ICGR analysis based on ORT provides more detailed prognostic insights.MethodsThis study retrospectively analyzed patients with acute ischemic stroke with anterior circulation large vessel occlusion (AIS-ACLVO) who underwent endovascular treatment (EVT) between January 2021 and December 2023. Their clinical characteristics, baseline and imaging data were recorded upon admission. Clinical outcomes were evaluated using the modified Rankin Scale (mRS) at 90 days post-procedure. The least absolute shrinkage and selection operator (LASSO) regression was employed for data screening. Multivariable logistic regression analysis was performed to explore the relationship between ICGR and 90-day (90d) clinical outcome. Additionally, a stratified analysis based on ORT was conducted to compare the diagnostic performance of ICGR and infarct core volume (ICV) at different time points.ResultsA total of 153 patients were included in the analysis. Univariate and Lasso regression analyses showed that the group with unfavorable outcomes had statistically significant differences in ICGR, age, history of atrial fibrillation, history of drinking, admission blood glucose level, Alberta Stroke Program Early CT Score (ASPECTS), and National Institutes of Health Stroke Scale (NIHSS) score compared to the favorable outcome group (all p < 0.05). Furthermore, multivariate logistic regression analysis indicated that ICGR was independently associated with clinical outcome in AIS-ACLVO patients [Odds Ratio (OR) 1.101, 95% confidence interval (CI) 1.029–1.178; p = 0.005]. When stratified by median ORT, the ICGR remained a strong predictor of outcome within 8 h (OR 1.188, 95% CI 1.048–1.347; p = 0.007), and proved to be a better predictor than ICV [area under the Receiver Operating Characteristic (AUROC) curve, 0.816 vs. 0.750, p = 0.024].ConclusionOur research indicates that the ICGR correlates with 90d clinical outcomes in AIS-ACLVO patients: a faster rate is associated with poorer outcomes. Within 8 h of ORT, the ICGR serves as a better predictor of 90d outcome than ICV.